СИСТЕМИ УПЕРЕДЖУВАЛЬНОГО КЕРУВАННЯ ІМПУЛЬСНИМИ ПЕРЕТВОРЮВАЧАМИ - Вербицький , Є.В. (Інститут електродинаміки НАН України, Київ, 2012)
Switching converters work features are analyzed. Quality improving methods of regulating electricity power are describing. General method of creating and adaptation predictive control systems for switching converters are considered. Structure of predictive control systems for switching converters are describmg. References 4, figure 1.